Traditional use of medicinal plants for Gastrointestinal Disorders: An Ethnobotanical study in Northern Tunisia - Hamrouni, Samar; Bensalem, Jamila; Jaffali, Chahrazed; Khadhri, Ayda; Aouadhi, Chedia (Ethnobotany Research and Applications, 2026)
Background: In rural areas of Tunisia and the wider Maghreb, where public healthcare services are limited and often expensive, traditional medicinal plants play a crucial role as primary and accessible sources of healthcare. They are particularly used to treat common gastrointestinal disorders such as gastroenteritis. Despite their importance, ethnobotanical knowledge in these regions remains insufficiently documented. Methods: An ethnobotanical survey was conducted in El Hamra, Amdoun region (Béja governorate, Tunisia) to collect and document data on the use of medicinal plants for the treatment of gastroenteritis. A total of 100 participants were interviewed using a well-structured questionnaire. The investigation focused on sociodemographic characteristics, the most frequently cited plant species, the parts of plants used, preparation methods, and the sources of traditional knowledge. Results: The findings revealed that women (57%) and young adults aged 20–30 years (33%) are the primary users of medicinal plants. Myrtus communis (52%) and Pistacia lentiscus (35%) were the most commonly cited species used against gastroenteritis. Leaves were the dominant plant parts employed (90%), typically prepared as decoctions (83%). Personal experience was identified as the main source of knowledge (45%), followed by the internet (30%) and reading (25%), indicating an interaction between traditional and modern information channels. Conclusions: This study highlights the ongoing relevance and transmission of ethnopharmacological knowledge in northern Tunisia. The frequent use of specific species across different regions emphasizes their potential for pharmacological investigation and sustainable exploitation. Overall, the documentation and validation of these traditional practices contribute to the preservation of local cultural heritage and support the development of new therapeutic resources derived from regional flora. Keywords: Ehnobotany, gastroenteritis, medicinal plants, Myrtus communis, Pistacia lentiscus, Tunisia